Evaluation of endometrial pathologies with high resolution transvaginal ultrasound - Shivde, Rajendra Shankar; Singh, Divya; Patel, Krutik; Mittal, Saurav; Prasla, Shopnil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The purpose of this study is to evaluate endometrial lesions on the basis of their appearances by high resolution trans-vaginal ultrasound. High resolution trans-vaginal sonography is useful for diagnosis of various endometrial lesions. Broad spectrum of endometrial lesions can be accurately imaged by various available modalities of which ultrasound is easily available, reliable, non-invasive and cost effective modality. Methods: In these study cases with complaints of abnormal uterine bleeding, suspected retained products, white discharge, dysmenorrhea and habitual abortions were evaluated with trans-vaginal ultrasound. Lesions were carefully studied and evaluated. Philips HD-11 and Accuson Siemens ultrasound machines with trans-vaginal probes were used. Results: In all 121 cases, trans-abdominal and trans-vaginal high resolution ultrasound was performed for different lesions in endometrium. Age group of females was between 18 to 65 years. Different uterine lesions were studied. Out of which most commonly encountered lesions were endometrial hyperplasia followed by polyps and least common lesion was AV malformation. Conclusions: High resolution trans-vaginal ultrasound helped in staging and management in cases of ca. endometrium. Hence trans-vaginal ultrasound should be 1st choice of investigation for diagnosis of endometrial lesions.